Turkey's Participation in International Biennials in the 1950s. (3rd July 2022) - Yıldız, Esra
Abstract: Biennials became important events for regeneration through culture and art in the post-WWII era, and as such they were supported through the cultural policies of nation-states. The Venice Biennale was first organized in 1895, and after 1950, other biennials took place in cities like Ljubljana, São Paulo, and Paris. Their number continued to increase over the years, as did the number of countries participating in them. In the atmosphere marked by the promotion of multiculturalism and world peace that followed the Second World War, Turkey was among the countries invited to take part in international biennials. However, because of economic and organizational challenges, it was only able to participate in such events from the 1950s onwards. In addition to Turkey's participation in international biennials as a country, individual artists who had left Turkey for various reasons took part in major exhibitions such as biennials and documenta during this period. This article focuses on Turkey's representation in the world art scene in the 1950s, when the country first began taking part in international biennials. It also questions why Turkey began participating in such events at that time and considers the impact they had on the Turkish art scene in the context of cultural policies of the Cold War. Drawing on new information and documents obtained from ASAC-Archivio Storico delle Arti Contemporanee, Fundação Bienal de São Paulo/Arquivo Histórico Wanda Svevo, Archives de la critique d'art, Rennes, Mednarodni Grafični Likovni Center (MGLC), and the Cincinnati Art Museum and Documenta Archiv, this study sheds light on Turkey's early participation in Ljubljana, International Biennial of Contemporary Color Lithography, Venice, São Paulo, and Paris Biennials as well as the inclusion of artists from Turkey in documenta, issues that have been little discussed in the literature on art history. By considering the imaginary boundaries that were drawn during the Cold War, Turkey's participation in international biennials in the 1950s, the global representation of Turkish artists at international exhibitions, and the incorporation of Turkish artists' works into the collections of major museums, it becomes clear that Turkey was an established part of the modern art movements of the period.